Stress driven high electrostrain at low field in incipient piezoelectrics. Issue 15 (December 2019) - Sheeraz, Muhammad; Khaliq, Abdul; Ullah, Aman; Han, Hyoung-Su; Khan, Aurangzeb; Ullah, Amir; Kim, Ill Won; Kim, Tae Heon; Ahn, Chang Won
Graphical abstract: Abstract: We use a strategy to reduce the driving electric field of the relaxor 0.72Bi1/2 Na1/2 TiO3 –0.28SrTiO3 (BNT–28ST) by introducing ferroelectric plate–type Bi1/2 (Na0.78 K0.22 )1/2 TiO3 (BNKT) particles. Consequently, 10 vol.% BNKT added BNT–28ST/BNKT (relaxor/ferroelectric) composite has delivered large normalized strain ( S max / E max = 650 pm/V) under relatively low applied field of 2.5 kV/mm with the reduction in the poling field value to 36% compared to that of pure BNT–28ST ceramics. We demonstrated that such behavior comes from the stress induced effect at the boundary of the ferroelectric and relaxor materials due to their different nature (relaxor/ferroelectric). The generation of stress is expected from the ferroelectric (BNKT) to the relaxor (BNT–28ST) at the boundary. Thereby, field–dependent stress at relaxor/ferroelectric phase boundary is monitored proposing the reduction of the poling field due to the strain coupling mechanism. Our findings provide a pathway for reducing the poling field in BNT–based incipient piezoelectric ceramics.